Thermal and optoelectronic properties of tyrosine-based methacrylate polymers via click chemistry with coumarin derivatives - Kane, Labouda; Seker, Ferhan Sultan; Amin, Murad Hiwa; Akman, Feride; Koran, Kenan; Biryan, Fatih (Elsevier, 2026)
In the present study, novel tyrosine-based methacrylate polymers were synthesized via copper-catalyzed azide-alkyne cycloaddition (CuAAC) reactions employing coumarin derivatives. The successful synthesis of the polymers was confirmed by FT-IR, 1H and 13C NMR spectroscopy. Comprehensive characterization was performed to assess their thermal stability, kinetic degradation behavior, and electrical properties. The average activation energies (Ea) for the thermal degradation of the synthesized polymers were calculated using the Flynn-Wall-Ozawa (FWO), Kissinger, and Tang methods. Notably, the incorporation of coumarin units resulted in a marked enhancement in thermal performance. The Ea value obtained via the FWO method increased from 143.99 kJ/mol for the unmodified poly(MA-Tyr(Boc)-PA) to 173.14 kJ/mol and 167.53 kJ/mol for the coumarin-functionalized click-1 and click-2 polymers, respectively. Optical properties were investigated using UV-Vis spectroscopy, where the modified polymers exhibited a characteristic absorption peak around 325 nm, indicative of the coumarin groups. Electrical performance was further examined through dielectric measurements. The dielectric constant significantly increased from 7.509 to 24.11, and electrical conductivity improved from 4.1783x10-9 S/cm to 9.3821x10-9 S/cm upon coumarin modification, underscoring their promise for optoelectronic and smart material applications. To evaluate the optoelectronic behavior, the ferrocenefunctionalized polymer (click-1) was integrated into a heterojunction device with the configuration Al/p-Si/ (click-1)/Al. The fabricated diode demonstrated a rectification ratio of 130, an ideality factor of 2.30, and a barrier height of 0.71 eV, indicating its potential for future electronic applications.
Keywords: Functional polymer; Coumarin; Click chemistry; Electrical properties; Thermal stability and kinetic